The Influence of Smart Learning Environment, e-Learning Platform, and Wearable Technology on Students' Microbiology Learning Independence - Putri, Yumna Syaza Kani; Ananta, Yorasakhi (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
The development of digital technology has brought innovations in higher education systems, including in microbiology education that demands conceptual understanding and independent skills. This article aims to systematically examine the influence of Smart Learning Environment (SLE), e-learning platforms, and wearable technologies on improving the learning independence of microbiology students. Through a literature study of various national and international scientific articles, it was found that the three technologies complement each other in creating an adaptive, interactive, and personalized learning ecosystem. SLE provides a data-based and artificial intelligence-based learning environment, e-learning platforms provide flexibility of access and multimedia content, while wearable technologies support real-time monitoring and feedback on learning. These findings provide a strong conceptual foundation for developing a digital learning model that encourages student learning autonomy in the field of microbiology. This article also formulates a hypothetical direction for further research based on educational technology in the life sciences.